In Vitro Regeneration, Ex Vitro Rooting and Foliar Stoma Studies of Pseudostellaria heterophylla (Miq.) Pax - Fengyun Wang; Xiaowei Xin; Hao Wei; Xiaohui Qiu; Boling Liu (Agronomy, 2020)
Pseudostellaria heterophylla, in the family Caryophyllaceae, is an important Chinese medicinal plant commonly used to treat various diseases in children and valued for its ornamental properties. In this study, nodal segments were obtained from wild plants and used as explants to develop an efficient micropropagation protocol for this species. Murashige and Skoog (MS) medium supplemented with 1.5 mg·L−1 6-benzyladenine (6-BA) was the most suitable medium for inducing axillary buds and enhancing their growth, and MS medium containing 0.1 mg·L−1 indole-3-butyric acid (IBA) was the most effective for inducing in vitro rooting. To reduce labor, time, and cost, microshoots were rooted under ex vitro conditions. Pretreatments of the shoots with 100 mg·L−1 naphthaleneacetic acid (NAA) for 1 min ensured successful rooting in 86.7% of shoots. Comparison of the leaf microstructure between in vitro- and ex vitro-rooted plantlets revealed abnormal stomatal apparatus in the former. The stomatal apparatus of ex vitro plantlets were normal, although the stomatal density was reduced, which indicated that these plantlets were more likely to be able to adapt to environmental conditions in the field. We identified the optimal medium for P. heterophylla multiplication with respect to increased rooting efficiency of micropropagated shoots under ex vitro conditions. This results presented here will be helpful for agricultural cultivation of P. heterophylla.